1998
DOI: 10.1007/s001340050770
|View full text |Cite
|
Sign up to set email alerts
|

Outbreaks of Staphylococcus aureus infections during treatment of late onset pneumonia with ciprofloxacin in a prospective, randomized study

Abstract: We carried out a prospective, randomized four-center study in nosocomial pneumonia to evaluate the clinical and microbiological efficacy and safety of different treatment regimens in adult intensive care patients. During the randomized treatment of 18 patients with late onset pneumonia, ciprofloxacin (CIP) was compared to ceftazidim plus gentamicin (CAZ/GM), outbreaks of Staphylococcus aureus infections occurred in center 1. This article reports the unexpected findings. In the CIP group six out of ten patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 5 publications
(2 reference statements)
0
20
0
1
Order By: Relevance
“…These findings are in accordance with the results of Harris et al [8], who found multidrug and lengthy antipseudomonal antibiotic exposures to be factors that predispose for the development of an infection with multidrugresistant P. aeruginosa. One pertinent finding is that recent exposure to a fluoroquinolone was also found to be an independent risk factor for carriage of and persistent colonization with methicillin-resistant Staphylococcus aureus [27][28][29]. This information could provide an extremely simple way to identify subgroups of patients from whom PRPA are likely to be isolated.…”
Section: Discussionmentioning
confidence: 92%
“…These findings are in accordance with the results of Harris et al [8], who found multidrug and lengthy antipseudomonal antibiotic exposures to be factors that predispose for the development of an infection with multidrugresistant P. aeruginosa. One pertinent finding is that recent exposure to a fluoroquinolone was also found to be an independent risk factor for carriage of and persistent colonization with methicillin-resistant Staphylococcus aureus [27][28][29]. This information could provide an extremely simple way to identify subgroups of patients from whom PRPA are likely to be isolated.…”
Section: Discussionmentioning
confidence: 92%
“…Interestingly, one recent study evaluating the relationship between the incidence of MRSA and the use of different classes of antimicrobials in Belgian hospitals found a correlation with increasing use of quinolones in a multivariate analysis (7). In another prospective randomized study, outbreaks of MRSA superinfections causing late-onset pneumonia were clearly associated with ciprofloxacin use in intensive care units (23).…”
Section: Discussionmentioning
confidence: 99%
“…One study showed that monotherapy with ciprofloxacin was as effective as therapy with a ␤-lactam and/or an aminoglycoside for the treatment of patients with documented Gramnegative sepsis (80). However, given that first-generation fluoroquinolones exhibit suboptimal activities against Grampositive bacteria, this class of antibiotics should not be used as empirical singleagent therapy in patients with severe sepsis.…”
Section: Monotherapy Vs Combination Antibiotic Therapymentioning
confidence: 98%